Aplikasi Pembayaran Menggunakan QR Ke Berbagai Negara Berbasis Android - Sofyan Mufti Prasetiyo; Fyona Apryanti; Khoiriyah; Rendi Pratama Juniar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In line with rapid technological developments, payment patterns and systems in economic transactions continue to change. Technological advances in the payment system have shifted the role of cash (currency) as a means of payment into a more efficient and economical form of digital payment. In its development, several countries have discovered and used an electronic payment product known as QR (Quick Response). Issues raised in this journal include how to make it easier to use QR Codes as a medium for payment transactions and transfer features not only to fellow users, but also to bank accounts. or users can withdraw their balances, be able to check balances at any time, besides that they can be used in various countries and are able to monitor spending and income balances in one based on an Android application.